Balance of CD4+IFNγ+ and CD4+CD25hiT cells as early predictor of a 3-month outcome in ischemic stroke patients - S. A. Morozov; M. A. Tikhonova; N. V. Pronkina; A. A. Shtobbe; O. Yu. Leplina; E. Ya. Shevela; A. A. Ostanin; E. R. Chernykh (Медицинская иммунология)
Early prediction for ischemic stroke (IS) outcome is a major challenge since it may help to optimize treatment program and  to make  it more  personalized. Since  T cells with  regulatory activity  are involved  in different  pathophysiological processes  in brain  stroke,  including inflammation, immune suppression, brain damage  and  repair, the  study  of T cells as potential biomarkers has essential  importance. The  present  work aimed to study the circulating T cell subsets with phenotype of type 1 T helper cells (Th1) and regulatory T cells (Treg), and their  ratio during  the acute  phase of IS, depending on stroke severity, inflammatory response  and 3-month outcome (according to modified Rankin scale, mRs).  Patients and methods. The study included 61 patients with a newly diagnosed IS (severity according to NIHSS ≥ 5), in the first 24-48 h after stroke onset, and 20 age/sex-related healthy  donors. Laboratory examination included assessment of leukocytosis, neutrophillymphocyte ratio  (NLR) and CRP  concentration. Mononuclear cells were isolated  from peripheral blood  to study T cell subsets. Th1 and Tregs were measured by FACS  analysis as CD4+IFNγ+  and CD4+CD25hiT cells, respectively. During the first 24-48 h after stroke, the patients had elevated values of leukocyte counts, NLR and CRP. Higher  levels of these parameters in severe stroke compared with mild stroke, as well as direct correlation of NIHSS with  NLR  and  CRP  evidenced that  the  stroke  severity  was associated with  more  pronounced inflammatory response. Patients were also characterized by a significant  decrease in CD4+IFNγ+Th1  cells, an  increase  in CD4+CD25hiTreg, and  a marked  decrease in Th1/Treg ratio.  Furthermore, in patients with NIHSS ≥ 8 (moderate and severe stroke), the percentage of CD4+IFNγ+T cells was in direct  correlation, and the number of CD4+CD25hiT cells was inversely related to CRP  and NLR  values. The changes of T cell subsets were more  pronounced in patients with  a favorable  3-month outcome (mRs  > 3). As a result,  the  patients with poor outcome (mRs  ≤ 3) had higher  CD4+IFNγ+T cell proportion, lower CD4+CD25hiT cell percentage and  4-fold  higher  CD4+IFNγ+/CD4+CD25hi  ratio  compared with opposing  group.  ROC  analysis  revealed  a “good” quality of prognosis  based on evaluation of the CD4+IFNγ+/CD4+CD25hi  ratio as a monopredictor of adverse outcome (AUC  = 0.75) and “very good”  quality  of prognosis  when the indicated ratio was combined with  NIHSS scale  (AUC  = 0.82).  The  data  obtained suggest  that  a decrease of Th1/Тreg ratio,  due  to  a decrease in CD4+IFNγ+  and increased CD4+CD25hiT cell counts  during the acute  phase of ischemic stroke is a compensatory reaction directed at inhibition of inflammatory response, and has a prognostic significance as early predictor of the outcome at 3 months.